Canada : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2004)
The government's strong monetary and fiscal policy framework, as well as the structural reforms introduced, have enabled the Canadian economy to respond flexibly to recent shocks and laid a solid foundation for recovery. Macroeconomic policies should remain supportive, with fiscal policy continuing to focus on sustained debt reduction and structural reforms geared toward boosting productivity. Canada's commitment to exchange rate flexibility has been helpful in facilitating the adjustment of global macroeconomic imbalances. Ensuring that regulatory and other policies support productivity, growth remains a key long-term challenge.